To transplant, or not to transplant? That is the question. A patient advocate evaluation of autologous stem cell transplant in neuroblastoma. Issue 8 (4th April 2022) - Bird, Nicholas; Scobie, Nicole; Palmer, Antonia; Ludwinski, Donna
Abstract: High‐dose chemotherapy with autologous stem cell transplant (ASCT) has been a mainstay of high‐risk neuroblastoma treatment for several decades, demonstrating improvements in event‐free survival but with risks of serious or even life‐threatening acute toxicities, severe long‐term adverse health effects for survivors, and ongoing contention regarding overall survival benefit. The merits of ASCT in the modern era of immunotherapy are a source of debate among parents, advocates, and some physicians. Here we examine evidence for and against ASCT, explore parent attitudes and their turmoil over decision‐making, and strongly encourage international research consortia to develop a coordinated strategy to accelerate progress toward a future that avoids the routine use of ASCT in high‐risk neuroblastoma.